An Analytical Study of P-Group, P-Subgroup and Different Cases of Sylow’s Theorems - Prasad, Binod (Academic Voices: A Multidisciplinary Journal, 2018)
This paper deals with the series of Sylow’s theorems and their applications. Actually First Sylow’s theorem provides the idea that whether a group has a sylow subgroup or not. The second Sylow’s theorem deals with conjugate subgroups of a Group and the third Sylow’s theorem provides the information about the number of Sylow’s subgroups.